Flash sale characteristics and attitude as determinant of impulse buying behavior - Asadiyah, Elia; Vania, Amelindha (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
Technological advances, driven by the increased use of the Internet and electronic commerce, are creating tremendous business opportunities. The use of flash sales as a medium for promotion and sales is one form of e-commerce use. This study examines the effects of promotion characteristics information, visualization, entertainment, and economic benefits on impulse buying. Quantitative methods with non-probability sampling techniques are used in the research. Data was collected from 240 respondents consisting of Gen Z in 9 cities in East Java using a five-point Likert scale through an online questionnaire. The results of the research show that information and visibility in flash sales can have an impact on attitudes, but entertainment information and economic benefits do not. There is evidence that customers' impulse buying behavior can be influenced by entertainment information and economic benefits. Therefore, it is recommended that future researchers re-examine the variables which do not influence. To increase customer interest and purchase intention, sellers should conduct flash sales at certain times or moments.